Phytase Activity and Isolation of the Phytase Gene of Mitsuokella Jalaludinii - Phang, Chiun Yee (2008)
Mitsuokella jalaludinii, a gram-negative, non-motile, non-spore-forming and rodshaped bacterium from rumen of cattle was used in this study. The bacterium showed the ability to produce phytase enzyme indicated by with the formation of a halo when it was grown on MF1 medium containing calcium phytate after incubation at 39oC for three days. The growth patterns of this bacterium in MF1 and MF1 + 0.5% Na-phytate media were similar, where the exponential phase was achieved after 6 h of incubation. The pH of the MF1 growth medium decreased from 7 to 4.96 while for MF1 + 0.5% Na-phytate medium, the pH decreased from 7 to 5.07. The phytase activity of M. jalaludinii was mainly present in the cell-bound fraction. The phytase activity was 4-fold higher when the bacterium was grown in MF1 + 0.5% Na-phytate medium compared to that of culture grown in MF1 medium. The phytase activity of the cell-bound fraction of culture grown in the MF1 + 0.5% Na-phytate medium was 3.1 U/ml but it was only 0.8 U/ml for the MF1 medium. The total inorganic phosphorus concentration in the MF1 + 0.5% Na-phytate medium did not inhibit phytase activity of M. jalaludinii. Four pairs of PCR primers were generated based on Selenomonas ruminantium’s phytase gene sequence. A partial phytase gene of M. jalaludinii with size 736 bp was successfully isolated using PCR amplification using its genomic DNA as template. Southern hybridization showed positive signals of genomic PstI fragment at sizes approximately 1.5 kb and between 4 to 5 kb by using the 736 bp clone as a probe. A size-selected genomic library at 1 to 2 kb was successfully generated. However, the phytase gene of M. jalaludinii was not successfully screened from the library using colony hybridization method. DNA walking approach was used to clone the 5’ end and 3’end of the phytase gene of M. jalaludinii. With a series of three steps of PCR amplifications, a 1.1 kb fragment was cloned and sequence. The Blastn results showed that the sequence contained part of the 5’ end sequence of the phytase gene. The 3’end sequence was also successfully obtained by using the same method where a 310 bp fragment was cloned and sequenced. Primers were generated based on the sequence information of 5’ end and 3’ end and a 1047 bp phytase gene was isolated from M. jalaludinii using PCR amplification method. Phylogenetic tree study indicated that M. jalaludinii phytase gene was not similar to other microbial phytase genes except to that of S. ruminantium JY35 phytase gene and they are indeed a novel phytase